Analisis pendapatan usaha pedagang kaki lima di sepanjang jalan Ir. H. Juanda Kelurahan mayang mangurai Kota Baru Kota Jambi - Agustina, Rohmah; Heriberta, Heriberta; Parmadi , Parmadi (e-Journal Perdagangan Industri dan Moneter, 2023)
This research aims to: 1) to determine and analyze the social and economic characteristics of food and beverage street vendors, 2) to determine and analyze the factors that influence the business income of food and beverage street vendors along Jalan Ir. H. Juanda Jambi City. The analytical tool used is quantitative descriptive. Based on the social and economic characteristics of food and beverage street vendors, it can be concluded that the average age of street vendors is 37 years, with a tendency for respondents to be male, have an average education level of high school, and have an average of 2 dependents. Based on the research results, it can be concluded that the average monthly income of food and beverage vendors in the research location is IDR 9,172,800, and the average monthly operational capital is IDR 12,262,300. The results of multiple regression analysis showed that the variables capital, working hours, length of business had a significant effect on the income of food and beverage vendors, while the business location variable had no significant effect on the income of food and beverage vendors.